9. Total colony of cellulolitic bacteria in the rumen of aceh cattle - Safika Safika; Siti Wardianah Matondang; Darmawi Darmawi; Mahdi Abral; Erina Erina; M Jalaluddin (Jurnal Medika Veterinaria, 2017)
The aim of this study was to count the total sum of cellulolitic bacteria colony in  aceh cattle rumen. The sample used was aceh cattle rumen liquid which taken from salughtered house in Banda Aceh. Aceh cattle rumen liquid were diluted from 10-2 to 10-5, then inoculated to agar BHM-CMC media with pour plate method. Petri dish was entered to candle jar to be incubated in an incubator with temperature 37oC about 96 hours. Colony of cellulolitic bacteria which were grown then were observed by using colony bacteria criteria (colour, position, edge, and diameter of colony), counting total of bacteria which was grown, and Gram staining. The results showed that there is a white translucent colony morphology, growth inside agar, smooth periphery, Gram-positive bacil. The average number bacteria of total bacteria in the cattle rumen liquid was 4,81 x 105 cfu/ml